2011
DOI: 10.1007/s12094-011-0670-5
|View full text |Cite
|
Sign up to set email alerts
|

PET-CT in the staging and treatment of non-small-cell lung cancer

Abstract: Positron emission tomography with 2-((18)F)-fluoro- 2-deoxy-D-glucose (FDG-PET) is a metabolic imaging technique. FDG-PET is more accurate than CT for the evaluation of mediastinal involvement in patients with nonsmall- cell lung cancer, offering a high negative predictive value. It can detect occult metastases in 11% of patients, although the etiology of the extrathoracic isolated uptakes needs confirmation. Theoretically, FDG-PET can influence the planning volume for radiotherapy, primarily in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 108 publications
0
14
0
Order By: Relevance
“…For instance, the partial volume effect (PVE), which is a consequence of the finite spatial resolution of the PET/CT scanner resulting in underestimation of the SUV of smaller lesions less than approximately 3cm in size (depending on several scanner-specific features) has the potential to generate false negatives, particularly when a lymph node in question is much smaller than a primary tumor or when assessing a lymph node containing only microscopic tumor deposits. 5 Along these lines, Gould et al showed that a smaller lymph node is more likely to be malignant than a larger lymph node when both have the same SUV. 10 This well-described phenomenon suggests that in order to derive clinically relevant information from the SUV of smaller lesions, one should correct the SUV for the size of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, the partial volume effect (PVE), which is a consequence of the finite spatial resolution of the PET/CT scanner resulting in underestimation of the SUV of smaller lesions less than approximately 3cm in size (depending on several scanner-specific features) has the potential to generate false negatives, particularly when a lymph node in question is much smaller than a primary tumor or when assessing a lymph node containing only microscopic tumor deposits. 5 Along these lines, Gould et al showed that a smaller lymph node is more likely to be malignant than a larger lymph node when both have the same SUV. 10 This well-described phenomenon suggests that in order to derive clinically relevant information from the SUV of smaller lesions, one should correct the SUV for the size of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22] Since false negatives and positives would be most common for an SUV close to a cutoff value, we selected the range of SUV max of 2.0 -6.0 for analysis so as to be inclusive of most commonly reported cutoff values of SUV max , which have typically ranged from 2.5 -5.3 in reported series. [3][4][5][6][7][8][9][10] Patients with a history of prior chemotherapy, radiation therapy, granulomatous disease, or non-skin cancer malignancy were excluded. Nodal pathology could be obtained by any means, including excisional biopsy (via mediastinoscopy, thoracotomy, etc.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Among several molecular imaging modalities, positron emission tomography (PET) is a promising technology that allows noninvasive imaging of tumor angiogenesis at the molecular level. 15 18 F-FDG is the most commonly used PET imaging agent and has been successfully applied for the diagnosis of many diseases worldwide. 16 However, 18 F-FDG is not a tumor-specific radiotracer and can lead to a false-positive in various forms of infection, inflammation, and granulomatous disease.…”
Section: ■ Introductionmentioning
confidence: 99%